2020
DOI: 10.3892/ijmm.2020.4555
|View full text |Cite
|
Sign up to set email alerts
|

A new threat from an old enemy: Re‑emergence of coronavirus (Review)

Abstract: The new outbreak of coronavirus from december 2019 has brought attention to an old viral enemy and has raised concerns as to the ability of current protection measures and the healthcare system to handle such a threat. It has been known since the 1960s that coronaviruses can cause respiratory infections in humans; however, their epidemic potential was understood only during the past two decades.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
189
0
10

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
5

Relationship

4
6

Authors

Journals

citations
Cited by 186 publications
(200 citation statements)
references
References 104 publications
(103 reference statements)
1
189
0
10
Order By: Relevance
“…SARS-COV-2: a brief summary. SARS-cOV-2 is part of the coronavirus family, as is SARS-coV-1 (which generated the 2003 SARS epidemic) and MERS-coV (which generated the MERS epidemic in 2013) (47).…”
Section: The Development Of a Covid-19 Vaccine: Current Trends And Prmentioning
confidence: 99%
“…SARS-COV-2: a brief summary. SARS-cOV-2 is part of the coronavirus family, as is SARS-coV-1 (which generated the 2003 SARS epidemic) and MERS-coV (which generated the MERS epidemic in 2013) (47).…”
Section: The Development Of a Covid-19 Vaccine: Current Trends And Prmentioning
confidence: 99%
“…In Europe there was a higher rate of severe cases in Italy (5,6) where 12% of positive patients were admitted to IcU vs. 5% in china; this difference was attributed to a higher proportion of elderly and increased social contact (7,8). Data from Germany (9) showed that ~1/3 of admitted patients had leucopenia and most of these (80%) had lymphopenia; c-reactive protein (cRP) was often increased and very high cRPs were associated with a less favorable outcome for the patient.…”
Section: Clinical Aspects Of Covid-19 Infections; Acute Respiratory Dmentioning
confidence: 99%
“…Clinically, infection with a coronavirus can be either asymptomatic or present with respiratory, gastrointestinal (GI), and neurological symptoms [ 7 ]. Four HCoVs, namely 229E, OC43, HKU1, NL63, are not considered to be very pathogenic [ 8 , 9 ], while the rest, Severe Acute Respiratory Syndrome-related Coronavirus (SARS-CoV) and Middle East Respiratory Syndrome-related Coronavirus (MERS-CoV) have caused two epidemics so far [ 8 , 10 12 ], and the novel SARS-CoV-2 caused the current pandemic [ 13 16 ]; all these viral strands can lead to acute respiratory failure.…”
Section: Introductionmentioning
confidence: 99%